Fourier transform infrared (FTIR) spectroscopy differentiation of lard and other shortening in puff pastry - Mohamed Rani, Wan Siti Farizan; Che Man, Yaakob; Ismail, Amin; Hashim, Puziah (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Spectra differentiation using Fourier transform infrared (FTIR) spectroscopy had been done individually on the three types of fats samples which contained the admixture of butter with lard (BL) and margarine with lard (ML) through attenuated total reflectance (ATR) accessory. Total fats that contain the admixtures were extracted from puff pastry prepared in laboratory by mixing 47g (wt/wt) of flour, 31.5g (wt/wt) of fat, 0.25g (wt/wt) of salt and 11.75g (wt/wt) of sugar prior to analyze by FTIR spectroscopy. While the lard were weight in range of 12.5–87.5% with the 12.5% increment. Total baked puff pastries were 21 samples. Using the combination of discriminant analysis (DA) and partial least square (PLS) the qualitative and quantitative of the fat profile were examined by assumed that the whole range of fat concentration of butter and margarine blended with lard was covered in this study at 1159 cm-1, 1115 cm-1 and 1096 cm-1 regions. Results showed the excellent binary mixture of BL and ML were achieved using PLS coupled with DA can be used to detect as low as 0.5% content of lard.